Splenomegaly in FOLFOX-naive stage IV or recurrent colorectal cancer patients due to chemotherapy-associated hepatotoxicity can be predicted by the aspartate aminotransferase to platelet ratio before chemotherapy - Miura, Kazuhiro; Nakano, Hiroshi; Sakurai, Joe; Kobayashi, Shinjiro; Koizumi, Satoshi; Arai, Tatsuhiro; Shimamura, Tsukasa; Makizumi, Ryoji; Yamada, Kyoji; Miyajima, Nobuyoshi; Otsubo, Takehito; Koike, Junki (International journal of clinical oncology, 2011)
Background Chemotherapy-associated hepatotoxicity is a common cause of postoperative complications after major hepatectomy. Splenomegaly may indicate portal hypertension due to chemotherapy. To identify chemotherapy-naïve patients with liver damage, the splenic volume (SV) and aspartate aminotransferase to platelet ratio (APR) were investigated. Methods Seventy-one patients receiving FOLFIRI, FOLFOX, or FOLFOX plus bevacizumab as first-line chemotherapy were included in this study. The SV measurement was performed by helical computed tomography volumetry, and the SV index (SVI) was calculated during 6 cycles of chemotherapy. The APR was used as an indicator of liver injury and the APR index (APRI) was calculated. Results The SVI and APRI were significantly higher in the FOLFOX group than in the FOLFIRI group. In the FOLFOX group, the maximum APR during FOLFOX administration was significantly higher in the subjects with SVI ≥ +30% than in those with SVI < +30% ( p < 0.01). The incidences of grade 3 or 4 adverse events and grade 2 or greater histopathological sinusoidal injury were significantly higher in the SVI ≥ +30% than in the SVI < +30% group. Interestingly, the SVI was significantly higher in the group with APR ≥ 0.17 before FOLFOX than in the subjects with an APR < 0.17 before FOLFOX ( p < 0.05). Conclusion Splenomegaly due to FOLFOX-associated hepatotoxicity can be predicted if the APR before FOLFOX is 0.17 or higher.